Recovery through resistance? nesting urban female song sparrows (Melospiza melodia) have a lower glucocorticoid response to disturbance and return to parental care as quickly as rural females - Lane, Samuel J.; Fossett, Taylor E.; VanDiest, Isaac J.; Sewall, Kendra B. (Frontiers in Physiology, 2025)
Urbanization represents a dramatic and relatively rapid change in the environment that has profound impacts on wild animals. Shifts in behavior and endocrine mechanisms of stress response could allow animals to successfully survive and reproduce in urban habitats. Numerous studies have examined the behavioral and physiological responses of territory-holding male songbirds to urbanization. However, breeding females likely experience anthropogenic noise, light at night, and human disturbance more frequently, and their behavioral coping responses to these disturbances are limited during incubation. Moreover, breeding females face higher energetic demands (allostatic load). Understanding how some species cope with novel urban habitats requires studying individuals facing the greatest challenges, such as breeding females. Therefore, we compared the glucocorticoid stress response and behavioral recovery from a disturbance between urban and rural female song sparrows (Melospiza melodia) during incubation. If facultative adjustments to the glucocorticoid stress response allow birds to cope with urban habitats, we predicted that urban females would return to parental care behaviors after a standardized stressor as soon or sooner than rural females, and that urban females would have a lower glucocorticoid response to the stressor. We captured female song sparrows at the end of the incubation period and measured their glucocorticoid (corticosterone) levels at baseline and after 30 min of standardized restraint. Concurrently, we installed radio frequency identification (RFID) systems at the nest to capture the time to return to parental care behaviors. We found that incubating urban females had significantly lower corticosterone levels when controlling for sampling timepoint (baseline and restraint-induced) compared to rural. Nest return times did not differ across habitats, and latency to return was not significantly correlated with corticosterone levels. Our findings are consistent with prior work in breeding male song sparrows at our study sites; urban males provide higher parental care and have lower restraint-induced corticosterone levels. The absence of a relationship between glucocorticoids and behavior makes it unlikely that these hormones directly regulate parental care, but lower corticosterone levels in urban birds could reflect stress resistance, which has been hypothesized to permit animals to breed in challenging or novel conditions such as urban habitats.